1997
DOI: 10.1038/bjc.1997.381
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical analysis of cisplatin-induced platinum-DNA adducts with double-fluorescence video microscopy

Abstract: SummaryTo detect low-level DNA platination, a sensitive immunocyto-and histochemical technique was developed using a polyclonal antibody. The antibody GPt, derived after immunization of rabbits with highly platinated DNA and purified with affinity chromatography, detected the main platinum (Pt)-containing intrastrand and interstrand adducts. Double-fluorescence microscopy image analysis was used to quantify Pt-DNA adducts with Hoechst 33258 fluorescence to locate the nuclei and with fluorescein isothiocyanate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Studies reported so far utilize fluorescence microscopy to visualize natively fluorescing drugs, such as daunorubicin [27], or ± in the case of non-fluorescing drugs such as cisplatin ± use for instance an immunocytochemical detection method to visualize cisplatin-DNA adducts in cells. For the latter technique, antibodies against Pt-DNA adducts have been generated [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported so far utilize fluorescence microscopy to visualize natively fluorescing drugs, such as daunorubicin [27], or ± in the case of non-fluorescing drugs such as cisplatin ± use for instance an immunocytochemical detection method to visualize cisplatin-DNA adducts in cells. For the latter technique, antibodies against Pt-DNA adducts have been generated [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Terheggen et al , developed a peroxidase-based immunoassay assay that was relatively insensitive, with an LOD of two adducts per 10 6 nucleotides, but compatible with quantitative determination of cisplatin–DNA adducts in tissue sections or cells from animals and cancer patients [145–149]. Meijer et al developed an immunohistochemistry assay that allowed the detection of cisplatin–DNA adducts at a single-cell level in buccal and tumor cells of patients [150]. Tilby et al [151] developed an ELISA method based upon a monoclonal antibody that was used to quantify carboplatin–DNA and cisplatin–DNA adducts formed in patients during therapy [120,121,152].…”
Section: Methods For Measuring Platinum Drug–dna Adducts From Clinicamentioning
confidence: 99%
“…The list of different DNA adducts which can be detected immunocytochemically is extensive (den Engelse et al . 1990; Meijer et al . 1997; Mistry et al .…”
Section: Detection Of Dna Damage Induced By Genotoxic Agentsmentioning
confidence: 99%
“…Also, the methylated bases O6-methylguanine and 7-methylguanine were immunocytochemically identified in rodent tissues after exposure to the tobacco-specific nitrosamine-4(methylnitrosamino)-1-(3-pyridyl)-1-butanone (Van Benthem et al 1994). The list of different DNA adducts which can be detected immunocytochemically is extensive (den Engelse et al 1990;Meijer et al 1997;Mistry et al 2003), but it is not in the scope of this review to cover this topic. Potentially, all these adducts that can be immnunocytochemically identified can be studied by multiparameter cytometry with respect to cell cycle phase specificity and induction of apoptosis.…”
Section: Immunocytochemical Detection Of Dna Adductsmentioning
confidence: 99%